SECONDARY METABOLITES OF THE SELECTED SPECIES OF MEDICINAL PLANTS IN THE RELATION TO THE PRODUCTIVE PARAMETERS OF LAYING HENS - Poracova, J.; Blascakova, M.; Salamon, I.; Zahatnanska, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The aim of our model experiment was to study the effect of chamomile essential oil (Matricaria recutita L.) and dried extract of Eleutherococcus senticosus MAXIM. on weight of laying hens Hisex braun and weight of eggs under cage system breeding conditions. In the experiment with chamomile essential oil, 16 hens were divided into two groups – a control group (CGCHA, n = 8) and one experimental group (EGCHA, n = 8); in the experiment with dried extract of Eleutherococcus senticosus MAXIM., 20 hens were divided into two groups – a control group (CGEL, n = 10), and one experimental group (EGEL, n = 10). The essential oil of chamomile and dried extract of Eleutherococcus senticosus in concentration of 0.1 % was administered to laying hens daily throughout one month. The laying hens were in good health condition throughout the experiment. The weight of laying hens and eggs in experimental group supplemented with chamomile essential oil and dried extract of Eleutherococcus senticosus MAXIM. increased insignificantly during 4 weeks of experiment.